Waste Analysis in the Hot Press Section Using the Qfm (Quality Filter Mapping) Method at Pt. Linggarjati Mahardika Mulia Pacitan - Nugroho, Galuh Ari; Muttaqin, Aan Zainal; Susanto, Doni (SEAN Institute, 2024)
PT. Linggarjati Mahardika Mulia is a company operating in the forestry sector located in Pacitan Regency, producing plywood with thicknesses ranging from 5mm, 8mm, 12mm, 15mm, 18mm. The subject of this research is the cause of waste in the hot press section of the pressing machine. The method used is Quality Filter Mapping because it is a relevant method for finding out the source of problems in the quality of the company's products. The results of this research showed that production in May with the highest percentage of plywood wastage occurred at a thickness of 15mm at 0.24% with a poor glue quality factor, and plywood with a thickness of 18mm at 0.24% for a damaged material factor. In June 2023, the highest wastage occurred in plywood with a thickness of 18mm at 0, 09% on the influencing factor is the quality of the glue is not good.